Implementasi Pasal 280 UU No 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Nurul Yaqin Kadir (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2021)
The purpose of this study is to determine the implementation Law No. 22 of 2009 concerning Road Traffic and Transportation as well as obstacles in implementing the provision in Biak’s jurisdiction. This research was an empirical juridical research. Interviews and observation are employed to collect data. Interviews were conducted by involving related parties, such as Biak’s Police and the Biak’s District Court. The results indicate that there are still many violations committed by a number of people who do not know Law No. 2 of 2009 particularly Article 280 concerning Road Traffic and Transportation in Biak Numfor. This is caused due to the lack of information in the local area regarding this regulation, so many people believe that the area is still in the vicinity of community settlements.